Impact of the terahertz and optical pump penetration depths on generated strain waves temporal profiles in a V2O3 thin film. (6th June 2022) - Huitric, Guénolé; Rodriguez-Fano, Michael; Gournay, Lucas; Godin, Nicolas; Hervé, Marius; Privault, Gaël; Tranchant, Julien; Khaldi, Zohra; Cammarata, Marco; Collet, Eric; Janod, Etienne; Odin, Christophe
Abstract : Strain waves generated in pump probe experiments through thermoelastic interaction modulate transient optical transmission. Terahertz uniform or optical exponentially decaying pump profiles effects are investigated in metallic thin film V2 O3 . Abstract : Triggering new stable macroscopic orders in materials by ultrafast optical or terahertz pump pulses is a difficult challenge, complicated by the interplay between multiscale microscopic mechanisms, and macroscopic excitation profiles in samples. In particular, the differences between the two types of excitations are still unclear. In this article, we compare the optical response on acoustic timescale of a V2 O3 Paramagnetic Metallic (PM) thin film excited by a terahertz (THz) pump or an optical pump, at room temperature. We show that the penetration depth of the deposited energy has a strong influence on the shape of the optical transmission signal, consistent with the modulation of permittivity by the superposition of depth-dependent static strain, and dynamical strain waves travelling back and forth in the sample layer. In particular, the temporal modulation of the optical transmission directly reflects the excitation profile as a function of depth, as well as the sign of the acoustic reflection coefficient between the film and the substrate. The acoustic mismatch between the V2 O3 layer and the substrate was also measured. The raw data were interpreted with a one-dimensional analytical model, using three fitting parameters only. These results are discussed in the context of triggering phase transitions by ultrafast pump pulses. To the best of our knowledge, this is the first report of the modulation of the optical transmission of V2 O3 with a THz pump within the acoustic timescale.